Low Affinity GPCRs for Metabolic Intermediates: Challenges for Pharmacologists - Smith, Nicola J. (Frontiers in Endocrinology, 2012)
The discovery that a number of metabolic intermediates can act through G protein-coupled receptors has attracted great interest in the field and has led to new therapeutic targets for a variety of diseases such as hypertension, type 2 diabetes, inflammatory disorders and metabolic syndrome. However, the low apparent affinity of these ligands for their cognate receptors poses a number of challenges for pharmacologists interested in investigating structure, function or physiology at these receptors. Furthermore, in each case, the endogenous ligands matched to their receptors have other, well established metabolic roles and thus selectivity is difficult to achieve. This review will discuss some of the issues researchers face when working with these receptors and highlight the ways in which a number of these obstacles have been overcome.